Scenarios of disaster, visions of liberation - Best, Steven (Quilmes, Argentina : Universidad Nacional de Quilmes, 2004)
As the planet spirals ever deeper into social and natural disaster, with all things becoming ever more tightly knit into the tentacles of global capitalism, there is an urgent need for new maps and compasses to help steer us into a viable mode of existence. Karl Marxś 1843 call for a ruthless criticism of everything existing has never been more urgent and appropriate, but all too often today critique is merely academic, stratospheres away from concrete action and progressive social policies. Yet, social critique and change in the slaughterhouse of capitalism needs to be guided and informed by powerful descriptions of what is -- the degraded forfeiture of human potential in a world where over a billion people struggle for mere existence -- but also by bold new visions of what can be, imaginative projections of how human beings might harmoniously relate to one another and the living/dying earth.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Descripción basada en Revista theomai, n. 10 (segundo semestre 2004), P. 11 sin numerar.
Recurso electrónico. Santa Fe, Arg.: elibro, 2023. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Democracia inclusiva; Globalización.; Artículos electrónicos.